2015
DOI: 10.4238/2015.september.28.2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of bifidobacteria on intestines in newborn rats with necrotizing enterocolitis and its regulation on TLR2 and TLR4

Abstract: ABSTRACT. We established a necrotizing enterocolitis (NEC) rat model and explored the role of bifidobacteria in the intestines of the rats and its regulation on intestinal Toll-like receptors (TLRs). Seventyfive newborn Sprague-Dawley rats were randomly divided into 5 groups (15 rats/group): group A, artificial feeding group (formula-fed); group B, NEC model (LPS + formula-fed); group C, bifidobacterium (LPS + formula-fed + bifidobacterium microcapsules, intragastric administration); group D, artificial feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
0
15
0
1
Order By: Relevance
“…Eleven studies were conducted in preterm animal models (42-52), 11 in term newborn animals (53-63), and the remaining 7 studied term animals at 2-4 weeks of age (42,(64)(65)(66)(67)(68)(69). Twenty-five studies used single-strain probiotics (42,43,(46)(47)(48)50,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) and four used multi-strain probiotics (44,45,49,51). The median sample size in the included studies was 72 (interquartile range: 36-96; range: ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies were conducted in preterm animal models (42-52), 11 in term newborn animals (53-63), and the remaining 7 studied term animals at 2-4 weeks of age (42,(64)(65)(66)(67)(68)(69). Twenty-five studies used single-strain probiotics (42,43,(46)(47)(48)50,(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70) and four used multi-strain probiotics (44,45,49,51). The median sample size in the included studies was 72 (interquartile range: 36-96; range: ).…”
Section: Resultsmentioning
confidence: 99%
“…The median sample size in the included studies was 72 (interquartile range: 36-96; range: ). Twenty-one of the 29 trials reported the incidence of histologically proven NEC (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(53)(54)(55)(56)(57)(58)(59)(64)(65)(66)(67) ( Supplementary Table S1). The remaining eight RCTs (52,(60)(61)(62)(63)(68)(69)(70) assessed the pathways of benefits of probiotics in reducing NEC but did not give data on the incidence, severity, or histology of NEC ( Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While rigorous mechanistic descriptions of the relationship between MAMPs, pattern-recognition receptors, and reductions in inflammation are lacking, one intriguing hypothesis is that beneficial bacteria might serve as physical barriers that block pathogenic MAMPs (e.g., lipopolysaccharides) from activating host pattern-recognition receptors such as TLR2 and TLR4 by binding to them instead, thereby preventing pro-inflammatory responses [95].…”
Section: Bacteria–brain Signallingmentioning
confidence: 99%
“…MAMPs are thought to trigger such anti‐inflammatory cytokines as IL‐10 by stimulating pattern‐recognition receptors (Chu and Mazmanian, ). In particular, some beneficial bacteria such as Bifidobacteria appear to prevent TLRs being activated and initiating a pro‐inflammatory response (Zhou et al ., ). Prebiotics and probiotics have been shown to interact with TLRs initiating both pro‐inflammatory and anti‐inflammatory responses (Takeda and Akira, ).…”
Section: Anti‐inflammatory Action and Immune Response And Its Role Inmentioning
confidence: 97%